Phylogenomic analysis of OXA-23-positive and genetic context of rare NDM-1-producing carbapenem-resistant Acinetobacter baumannii isolates in a teaching hospital in China - Dong, Su; Lou, Jianjiang; Mao, Caiping; Fang, Yuejuan; Zhang, Huan (Frontiers in Microbiology, 2025)
Nosocomial outbreaks caused by carbapenem-resistant Acinetobacter baumannii (CRAB) strains are rapidly emerging worldwide and are a cause for concern. In this study, a phylogenetic tree of 18 A. baumannii strains collected from a teaching hospital in China was constructed to explore the genetic relationship in the context of genomic insights. The study also aimed to explore the relationship among the strains and to assess the potential spread within the teaching hospital. All CRAB strains were collected from 17 patients, with the majority obtained from sputum samples (55.56%, 10/18). Moreover, 61.11% (11/18) of the CRAB strains were collected from the intensive care unit (ICU). Whole-genome sequencing (WGS) was performed using the Illumina and Oxford Nanopore platforms, and the bioinformatic analysis was subsequently performed. Based on the Pasteur multilocus sequence typing (MLST) scheme, 16 A. baumannii strains were classified as sequence type 2 (ST2). The remaining two A. baumannii strains belonged to two rare sequence types (STs), namely ST34 and ST23, respectively. KL and OCL analysis showed that the majority of the strains (61.11%, 11/18) contained KL7. Whole-genome sequencing revealed that 16 CRAB strains were OXA-23 producers, while the remaining two strains carried blaNDM-1 and blaOXA-72. Genetic structure analysis showed the context of blaNDM-1 was ISAba14-aph(3′)-VI-ISAba125-blaNDM-1-ble-MBL. Comparative genomics analysis revealed that 16 CRAB strains (ST2_Pas) had a close genetic relationship, and 8 CRAB strains possessed the same resistance gene profile, with only 1–6 SNPs observed among them. Therefore, there is an urgent need for increased surveillance of both patients and the hospital environment to prevent and control the spread of CRAB.